Logitech / Mohamad Ajwad Mohd Sobri - Mohd Sobri, Mohamad Ajwad (2022)
The goal of this project is to find the problem in the product. The company I've chosen is Headset for my inquiry. I used a SWOT analysis to determine H600's strengths, weaknesses, opportunities, and threats in this case study. The first issue I observed with the H600 Wireless Headset is that it interferes with Bluetooth and Wi-Fi connections, resulting in a poor user experience. I've come up with the best solution to the problem: Create a headset with features that will not interfere with a wireless device, which is far more practical and provides a far better hearing experience for the user.